2016
DOI: 10.1530/jme-16-0001
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide alters DPP4 in the circumvallate papillae of type 2 diabetic rats

Abstract: Liraglutide, a human glucagon-like peptide (GLP1) analog that partially inhibits dipeptidyl-peptidase 4 (DPP4), can decrease glucose levels and suppress appetite in patients with type 2 diabetes (T2DM). GLP1 and its receptor (GLP1R) also exist in the taste buds of rodents and regulate taste sensitivity. DPP4, a protease, functions in homeostasis of blood glucose, lipids, and body weight. Interactions among GLP1, GLP1R, and DPP4 likely affect taste and food-intake behavior. The aim of the present study was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…Liraglutide upregulated the expressions of DPP-IV in taste buds and downregulated the same in the hypothalamus of T2DM rats. 8 Our study has also shown the effect of Liraglutide on DPP-IV activity. It significantly reduces the activity of DPP-IV in plasma of day 1 and day 21 group.…”
Section: Resultssupporting
confidence: 52%
“…Liraglutide upregulated the expressions of DPP-IV in taste buds and downregulated the same in the hypothalamus of T2DM rats. 8 Our study has also shown the effect of Liraglutide on DPP-IV activity. It significantly reduces the activity of DPP-IV in plasma of day 1 and day 21 group.…”
Section: Resultssupporting
confidence: 52%
“…This study exhibited the liraglutide administration in the constructed IR animal and cell models, and confirm that liraglutide had a good therapeutic effect in obesity-associated IR. Previous studies have reported the regulatory effect of liraglutide on the expression of DPP4 in T2DM 28. In the current study, we observed that the increased DPP4 in the adipose tissues and adipocytes under IR status was significantly reduced by the treatment of liraglutide, which is consistent with the previous study.…”
Section: Discussionsupporting
confidence: 92%
“…Liraglutide is a kind of incretin-based drug, which has been widely used in the treatment of T2DM with obesity 27. Cao et al indicated that liraglutide administration in T2DM resulted in abnormal DPP4 expression 28. Our previous studies have reported that AMPK was up-regulated in adipocyte with liraglutide in db/db mice 29.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, it was believed that TBs do not express an enzyme DPP4 that rapidly catabolizes active GLP-1 [24]. Later, DPP-4 immunoreactive cells localized in the rat taste buds with significantly higher expression of DPP-4 mRNA in the rats with diabetes [74].…”
Section: Glp-1 In the Taste Budsmentioning
confidence: 99%